Peningkatan Prestasi Belajar Bahasa Inggris melalui Metode Mind Mapping di MAN 1 Yogyakarta - Surini Surini (Jurnal Pendidikan Madrasah, 2022)
This study aims to analyze the application of assignments using the mind mapping method. Assignments are expected to help understanding and increase student activity. The subject of the study was a student of class XII MIPA 2 MAN 1 Yogyakarta. The method used in this study is a class action research method. The study took place in two cycles. Each cycle follows the procedures of planning, implementing, observing and reflecting. From the results of the study, in the first cycle students who obtained a score of > 7.00 reached 54.54% with sufficient categories. Meanwhile, in cycle II, students who obtained a score of > 7.00 reached 81.81% with an active category. The method of assigning assignments to make mind mapping a certain text can improve the ability to master English vocabulary in students optimally.